Intercultural Health and Dentistry - Ramírez, Abdrés Sebastián (Journal of Oral Research, 2019)
Apropos of the new regulation on public policies of Intercultural Health, called “Systematization of the proposals of the native peoples to receive health care with cultural pertinence”, the Commission for Interculturality in Dentistry of the University of Conception raised the need to share the construction of this regulation.